2003
DOI: 10.1097/01.prs.0000076193.67701.6a
|View full text |Cite
|
Sign up to set email alerts
|

Penoscrotal Extramammary Paget???s Disease: A Review of 33 Cases in a 20-Year Experience

Abstract: Extramammary Paget's disease in men most frequently involves the penoscrotal area. The uncertainty of the outcome and of the relationship to the underlying adnexal carcinoma and associated internal malignancy still exists. From 1982 to 2001, 33 patients with penoscrotal extramammary Paget's disease were treated and followed up. Therapeutic modalities included carbon dioxide laser ablation (two patients) and local wide excision (31 patients). Split-thickness skin graft (22 patients), local scrotal flap (six pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 26 publications
3
77
5
Order By: Relevance
“…Invasive genitourinary tract cancers (prostate, bladder, kidney) [22][23][24][25][26][27][28] or gastrointestinal sites (colon, rectum, liver) 29,30 can be associated, synchronously or metachronously, with penoscrotal empd, but the frequency of this association is not consistently reported. In a recent M.D.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive genitourinary tract cancers (prostate, bladder, kidney) [22][23][24][25][26][27][28] or gastrointestinal sites (colon, rectum, liver) 29,30 can be associated, synchronously or metachronously, with penoscrotal empd, but the frequency of this association is not consistently reported. In a recent M.D.…”
Section: Discussionmentioning
confidence: 99%
“…In general, wide local resection might be the best choice for EMPD because it offers the possibility of a cure [ 1 ] . The prevalence of local recurrence after wide local resection of penoscrotal EMPD has been reported to be 19.4 -27.3% of patients [ 3,4,7 ] . Early studies by our research team indicated that frozen section-guided wide local resection produces an acceptable prevalence of recurrence (16%) when treating penoscrotal EMPD.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,14 In this report, we introduce the 'anterolateral thigh perforator flap' technique to reconstruct defects after the resection of penoscrotal EMPD lesions. The anterolateral thigh flap is an effective option for the reconstruction of soft-tissue defects such as those in the head, neck, extremities, perineal and scrotal areas.…”
Section: Surgical Treatmentsmentioning
confidence: 99%
“…The primary treatment is surgical excision. 7,9,11,[14][15][16][17] Non-surgical methods are also used but only in a few cases. Hata reported that radiotherapy was a curative therapy in 22 patients with EMPD.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation